The Impact of the ChatGPT Platform on Consumer Experience in Digital Marketing and User Satisfaction - PAVLOVIĆ, Nikola; SAVIĆ, Marko (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024, 2024)
ChatGPT, an artificial intelligence (AI) chat platform, facilitates conversation between humans and bots. By integrating machine learning and natural language processing, it revolutionizes the way people interact with AI. Many people are excited about using ChatGPT because it has numerous potential applications and advantages compared to other similar programs. Therefore, this paper demonstrates that, in line with specific ethical considerations, ChatGPT has enormous potential to revolutionize and shape the future of marketing. We begin by questioning whether ChatGPT has a significant impact on consumer experience in digital marketing and overall user satisfaction. The methods used in the study include descriptive and inferential statistical methods, as well as the OLS method. The results show that the use of ChatGPT is continuously rising and increasingly being implemented in various industry segments, particularly in the field of digital marketing. Automation of customer care, increased productivity, automated research, and better understanding of consumers are ways it can assist marketing professionals.